Developing a suicide prevention action plan in Kisumu County, Kenya - Sarah Atieno Ouma; Florina Frey; Gregory Ganda; Beryl Annie Arogo; Douglas Onyango Otieno; Paul Andrä; Rick Peter Fritz Wolthusen (Wiley, 2023)
Abstract Suicide prevention is a complex and context‐dependent challenge. About 75% of deaths by suicide occur in low‐ and middle‐income countries; yet, most current suicide prevention strategies build upon data from high‐income countries (HIC). The Kisumu County Government (KCG) in Kenya recognized the need for a suicide prevention action plan. In the absence of a Kenyan national suicide strategy, it also did not solely depend on recommendations from HIC. The KCG therefore convened a multidisciplinary workgroup with stakeholders from various sectors that led the development of the Kisumu County Suicide Prevention Action Plan (KCSPAP). The team utilized a mixed‐method approach (literature review, a desk review of mental health indicators and death certificates, focus group discussions, and key informant interviews) identifying the following: (a) magnitude and variations of suicide cases (higher number of suicide completions compared to attempts; the leading method was organophosphate poisoning though the suicide method often was not specified); (b) protective and risk factors (male gender, being between 19 and 45 years of age, and being married); (c) community perceptions of suicide (taboo topic; associated with negative spirits; community members were divided on suicide decriminalization); (d) potential solutions (need for data collection, awareness creation; scale‐up of traditional and nontraditional mental health approaches). Given the importance of a public health perspective on suicide prevention, the data in the KCSPAP are organized in a public health prevention framework that builds on a data collection framework. The KCSPAP was handed over to the KCG in mid‐2020; different recommendations have been implemented since. The KCSPAP is an example of policymaking based on local knowledge. This homegrown policymaking approach has multiple benefits and can be used by stakeholders locally and in other countries.